A rare case of surgical obstructive jaundice due to spontaneous gastro-gastric intussusception - Bhalerao, Aishwarya S.; Kumar, Supreet; Shah, Suryalok P.; Pandey, Alok K.; Tandon, Vivek; Govil, Deepak (International Surgery Journal, 2024)
Intussusception in adult patients is far less common than in paediatric population. In adults, the small bowel is the most common site of intussusception and stomach or a surgical stoma as the site of intussusception is unusual. Epidemiological data specifically related to gastrogastric intussusception is extremely rare. When an adult develops intussusception, they typically present with nonspecific symptoms like vomiting, pain abdomen and abdominal distention. Abdominal mass and features of intestinal obstruction which are the common modes of presentation in paediatric patients are infrequently encountered in adult patients. Foregut intussusception is usually caused by either gastric polyps passing through the pylorus into the duodenum or intussusception of the gastric remnant through a surgically fashioned gastro-jejunal anastomosis. There have never before been any reports of a true gastro-gastric intussusception, according to a search of the MEDLINE database. We present a case of a 38-year-old gentleman who presented with gastro-gastric intussusception due to a large polypoidal mass arising from the greater curvature of stomach which had prolapsed into the duodenum hence acting as a lead point with resultant gastric outlet obstruction and extrinsic compression on the retro duodenal portion of the common bile duct, leading to surgical obstructive jaundice which subsided after surgical resection without the need for any hepato-pancreatic intervention like biliary stenting. The rarity of gastro-gastric intussusception with the offending intussusceptum causing obstructive jaundice makes this case one of its kind and worthy of publication.